The student and faculty awareness and use of the guidance services of St. Anthony School - Reyes, Lina O. (Animo Repository, 1979)
This is a study of the student and faculty awareness and use of the existing guidance services of St. Anthony School with the end in view of improving them. Furthermore, it attempts to offer an in-service training program to develop among teachers of the said school guidance consciousness and the realization of the need for more involvement in the said program. Attempting to evaluate the existing guidance services the researcher aimed to answer the following questions: 1) Are the students aware of the existence of the guidance services? 2) Do students avail of the guidance services? 3) Are the teachers aware of the guidance services? 4) Do the teachers made use of the services available in the guidance office? 5) Are the teachers willing to be trained as teacher counselors? 6) What program can be adopted to enable the teachers to acquire skills in guidance work? To realize this objective of the study, a descriptive survey was used. The instruments used were the modified questionnaires adopted from Poirier and Villar. There were two sets of questionnaires. The first set was distributed to two hundred fourteen randomly selected students which comprised the ten percent of the total population from grade three to fourth year. The second set was given to seventy teachers, but only sixty-seven turned in the answers. Presented in frequency, the data were treated by percentage. There was no necessity of using sophisticated designs since the data could be easily treated by percentage to get inferences for the discussion of the result. To facilitate also the understanding of the discussion, tables are used. Based on the survey findings, the following conclusions are drawn: 1) Generally, the students were aware of the existence of guidance services. However, the study revealed that there is a need to orient the elementary students about these services. 2) In spite of their knowledge about the existing guidance program, the students are not sold to using such services. 3) The students received an average assistance from the school personnel-principal, counselors, deans and teachers, as revealed by the overall students' evaluation on the extent of assistance they get from school personnel. However, they felt that no assistance was practically given to them in the interpretation of their psychological test results and little assistance in the choice of vocation or career. 4) The faculty members know that guidance services are offered by the school, however, their knowledge of such stops on mere existence. 5) Since the teachers do not know what data are available in the guidance office, the importance of such data and their uses, they do not make use of them. 6) Aware of their guidance responsibilities as classroom teachers, the faculty members of St. Anthony School are willing to acquire knowledge and skills in guidance and counseling. 7) To enable the teachers to acquire and develop skills needed to become classroom counselors, an in-service training program can be adopted.